Money talks explaining how money really works - Bandelj, Nina; Wherry, Frederick F.; Zelizer, Viviana A. Rotman (Princeton University Press, 2017)
The world of money is being transformed as households and organizations face changing economies and new currencies and payment systems like Bitcoin and Apple Pay gain ground. What is money, and how do we make sense of it? Money Talks is the first book to offer a wide range of alternative and unexpected explanations of how social relations, emotions, moral concerns, and institutions shape how we create, mark, and use money. This collection brings together a stellar group of international experts from multiple disciplines--sociology, economics, history, law, anthropology, political science, and philosophy--to propose fresh explanations for money's origins, uses, effects, and future. Money Talks explores five key questions: How do social relationships, emotions, and morals shape how people account for and use their money? How do corporations infuse social meaning into their financing and investment practices? What are the historical, political, and social foundations of currencies? When does money become contested, and are there things money shouldn't buy? What is the impact of the new twenty-first-century currencies on our social relations? At a time of growing concern over financial inequality, Money Talks overturns conventional views about money by revealing its profound social potential.